LHC - Chaves-Castillo, Andrea (Instituto Tecnológico de Costa Rica, 2017)
Housing is a subject that must be continuously analyzed from the architectural perspective. Human needs change, the way we interact and live varies. The ´Curridabat Housing Laboratory´ project analyzes housing-city-legislation- as related issues, understanding the importance of these as a whole. Starting with the characteristics provide by the modification of the Land Use Planning Code of the town of Curridabat, an urban and architectonic analysis was carried out for the elaboration of a collective housing project, going through different urban scales and knowing the spatial repercussion of this legislation. The trends of this type of housing were studied, a sector was selected through an experimental methodology and two properties were used for the design of the architectural proposal. Each scale of analysis in the project generated conclusions, inviting to rethink and explore how we can inhabit the city in a more sustainable and diverse way.
Laboratorio habitacional de Curridabat, anteproyecto de vivienda colectiva
Proyecto de graduación (Licenciatura en Arquitectura y Urbanismo) Instituto Tecnológico de Costa Rica, 2017
Keywords: Curridabat (Costa Rica); Vivienda multifamiliar; Arquitectura doméstica; Multifamiliares